Impact of TREM1 Variants on the Risk and Prognosis of Glioma in the Chinese Han Population - Hu M; Wei J; Hao J; Jin T; Li B (Dove Medical Press, 2023)
Mingjun Hu,1- 4 Jie Wei,1- 3 Jie Hao,1- 3 Tianbo Jin,1- 3 Bin Li1- 3 1College of Life Sciences, Northwest University, Xi'an, Shaanxi Province, People's Republic of China; 2Provincial Key Laboratory of Biotechnology of Shaanxi, Northwest University, Xi'an, Shaanxi Province, People's Republic of China; 3Key Laboratory of Resource Biology and Biotechnology in Western China, Ministry of Education, Northwest University, Xi'an, Shaanxi Province, People's Republic of China; 4Department of Neurosurgery, Xi'an Chang'an District Hospital, Xi'an, Shaanxi Province, People's Republic of ChinaCorrespondence: Mingjun Hu, College of Life Sciences, Northwest University, #229, Taibai North Road, Xi'an, Shaanxi Province, 710069, People's Republic of China, Tel +86-15339228629, Email slhmj@tom.comBackground: Glioma is the main pathological subtype of brain tumors with high mortality.Objective: This study aimed to elucidate the correlation between TREM1 variants and glioma risk in the Chinese Han population.Methods: Genotyping of six variants of TREM1 was completed by Agena MassARRAY platform in 1061 subjects (503 controls and 558 glioma patients). The relationship between TREM1 polymorphisms and glioma risk was calculated using the logistic regression model, with odds ratio (OR) and 95% confidence intervals (CIs). A multifactor dimensionality reduction (MDR) method was performed to assess SNP-SNP interactions to predict glioma risk.Results: In this research, overall analysis illustrated an association between TREM1 rs9369269 and an increased risk of glioma. Rs9369269 was also related to the risk of glioma in patients aged ≤ 40 years and females. Subjects with rs9369269 AC genotype were likely to obtain glioma compared to people with CC genotype (patients with astroglioma vs healthy people). Compared to TT genotype carriers, carriers with AT genotype of rs1351835 were significantly associated with overall survival (OS).Conclusion: Taken together, the study identified the association between TREM1 variants and glioma risk and TREM1 variants were significantly associated with the prognosis of glioma. In the future, larger samples are needed to verify the results.Keywords: glioma, TREM1, single nucleotide polymorphisms, risk